Can comprehensive specialised end‐of‐life care be provided at home? Lessons from a study of an innovative consultant‐led community service in the UK. (15th April 2014) - Noble, B.; King, N.; Woolmore, A.; Hughes, P.; Winslow, M.; Melvin, J.; Brooks, J.; Bravington, A.; Ingleton, C.; Bath, P.A.
<x xml:space="preserve">Abstract</x> The Midhurst Macmillan Specialist Palliative Care Service (MMSPCS) is a UK, medical consultant‐led, multidisciplinary team aiming to provide round‐the‐clock advice and care, including specialist interventions, in the home, community hospitals and care homes. Of 389 referrals in 2010/11, about 85% were for cancer, from a population of about 155 000. Using a mixed method approach, the evaluation comprised: a retrospective analysis of secondary‐care use in the last year of life; financial evaluation of the MMSPCS using an Activity Based Costing approach; qualitative interviews with patients, carers, health and social care staff and MMSPCS staff and volunteers; a postal survey of General Practices; and a postal survey of bereaved caregivers using the MMSPCS. The mean cost is about 3000 GBP (3461 EUR) per patient with mean cost of interventions for cancer patients in the last year of life 1900 GBP (2192 EUR). Post‐referral, overall costs to the system are similar for MMSPCS and hospice‐led models; however, earlier referral avoided around 20% of total costs in the last year of life. Patients and carers reported positive experiences of support, linked to the flexible way the service worked. Seventy‐one per cent of patients died at home. This model may have application elsewhere.